Near Complete Reversal Of Large Diffusion-Weighted Imaging Lesion After Thrombectomy: A Case Report And Literature Review - Huy Quang Dang; Trung Quoc Nguyen; Duc Nguyen Chiem; Tra Vu Son Le; Ryan Anh-Quang Nguyen; Huy Nguyen; Thang Huy Nguyen (Cerebrovascular Diseases Extra)
Introduction: Diffusion-Weighted Imaging (DWI) plays a crucial role in acute ischemic stroke (AIS), as it is used to evaluate the ischemic lesions that are irreversibly damaged. The reversibility of DWI ischemic lesions has been noted in patients with AIS who undergo revascularization therapy. In addition, the occurrence of this phenomenon in large ischemic regions remains rare, particularly the near-complete reversal of large DWI lesion cases. Case Presentation: A 58-year-old male presented with a generalized tonic-clonic seizure. Emergent magnetic resonance imaging (MRI) revealed an extremely large infarction lesion in the right hemisphere with an Alberta Stroke Program Early Computed Tomographic Score (ASPECTS) value of 2 and occlusion of the terminal right internal carotid artery. The patient was immediately transferred to the Digital Subtraction Angiography (DSA) Unit for endovascular treatment with a stent retriever. After a rapid successful reperfusion with expanded treatment in cerebral infarction (eTICI) score of 3, the patient promptly recovered 24 hours after the procedure. A brain MRI was repeated after 8 days of admission, and interestingly, the DWI lesion showed significant reversal. The modified Rankin scale (mRS) at discharge was 2 and 1 at 90-day follow-up, respectively. Conclusions: Our case shows that the reversibility of DWI ischemic lesions can occur during the acute stroke phase, even in patients with extremely large regions, if rapid and successful reperfusion is achieved. The clinical implications of this phenomenon indicate that using DWI to evaluate the infarct core should be interpreted with caution.